George P. Fisher papers - Fisher, George P. (George Purnell), 1817-1899.
Correspondence, speeches, essays, legal records, commissions, biographical sketches, and other papers relating to Fisher's legal career and other subjects. Letters to Fisher from John M. Clayton concern Delaware politics, Oregon boundary question, Mexican War, and opposition to Clayton as U.S. secretary of state. Other correspondence pertains to the legal practice of Nicholas Ridgely of Delaware. Includes an essay by Fisher on the trial of John H. Surratt for plotting to assassinate Abraham Lincoln. Correspondents include James Buchanan, Henry Clay, John J. Crittenden, Ann Ridgely Du Pont, Hannibal Hamlin, Edward Joy Morris, Frederick William Seward, Daniel Webster, and Thurlow Weed.
Public official and judge of the supreme court of the District Columbia.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index of the general correspondence and special correspondence of others available in the Library of Congress Manuscript Reading Room and at
Keywords: Buchanan, James, -- 1791-1868 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Clayton, John M. -- 1796-1856.; Clayton, John M. -- 1796-1856 -- Correspondence; Crittenden, John J. -- 1787-1863 -- Correspondence; Du Pont, Ann Ridgely, -- 1815-1898 -- Correspondence; Hamlin, Hannibal, -- 1809-1891 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Assassination; Morris, Edward Joy, -- 1815-1881 -- Correspondence; Ridgely, Nicholas, -- 1762-1830.; Seward, Frederick William, -- 1830-1915 -- Correspondence; Surratt, John H. -- 1844-1916 -- Trials, litigation, etc; Webster, Daniel, -- 1782-1852 -- Correspondence; Weed, Thurlow, -- 1797-1882 -- Correspondence; District of Columbia. -- Supreme Court (1863-1936); Courts -- Washington (D.C.); Mexican War, 1846-1848.; Practice of law -- Delaware; Practice of law -- Washington (D.C.); Trials (Conspiracy); Delaware -- Politics and government; Oregon -- Boundaries; Jurists; Public officials